Blade of secrets - Levenseller, Tricia (Bladesmith, 2021)
"In the first book in Tricia Levenseller's exciting new YA fantasy duology, a teenage blacksmith with social anxiety is forced to go on the run to protect the world from the most powerful magical sword she's ever made"--